On the Stability Problem in Fuzzy Banach Space - G. Zamani Eskandani; P. Găvruţa; Gwang Hui Kim (Abstract and Applied Analysis)
We investigate the generalized Ulam-Hyers stability of the Cauchy functional equation and pose two open problems in fuzzy Banach space.